Social Entrepreneurship (SE) Development in Bangladesh (Global Journal of Management and Business Research, 2015)
The paper presents the results of a survey during the period of 2012-1013 that has been carried out by us in order to examine the potentiality of the social entrepreneurship development. The samples covered in this study were social entrepreneurs. The total numbers of social entrepreneurs are 50 by taking 10 from each village of Sitakunda Thana in Chittagong on the basis of purposive sampling. Empirical survey portrays the prevalence of potentialities for social entrepreneurship development in the study areas. Many problems in implementation of the social entrepreneurship development programme have been identifies such as lack of support for social entrepreneurs, inadequate motivational training, absence of capacity building programme of social entrepreneurship, ineffective campaign programmes, absence of network among government, Philanthropist other stakeholders, absence of effective management information system and lack of research on social entrepreneurship in study areas.